Matabeleland,1890
includes letters from: David Carnegie (secretary), Hope Fountain and Palapye - forwards report from John Moffat; return to Hope Fountain William Allan Elliott, Bulawayo and Palapye - interview with Lobengula and Dr Jameson; had to leave Inyati [Nyathi]; describes Mashona tribes; hoping to return to Inyati Charles Helm, Crocodile river, Setlagoli, Kimberley, Cape Town and Makeking [Mafikeng] - permission from Chief for Matabele concession to prospect in Mashonaland Bowen Rees, Cape Town and Inyati William Ashton, Barkly West - fears for Matabeleland James Hepburn, Palapye - Matabeleland missionaries returned to stations